Development of A Learning E-Module Based on The OIDDE Learning Model on The Material on The Classification of Living Things in Class VII of Muhammadiyah 08 Junior High School, Kota Batu - Hanik Fitrotul Azizah; Atok Miftachul Hudha; Fendy Hardian Permana (Journal of Educational Sciences, 2026)
The demands of 21st-century education require integrating technology and innovative learning models. This study aims to develop a valid and practical e-module based on the OIDDE (Orientation, Identify, Discussion, Decision, and Engage in Behavior) learning model for living creature classification material in class VII at Muhammadiyah Junior High School 08 Batu City. The ADDIE (Analysis, Design, Development, Implementation, Evaluation) model guided the development process. Data were collected through validation sheets from material, media, and language experts, and practicality questionnaires completed by educators and students. The e-module was validated by six experts and tested on 26 students. Validation results showed mean scores of 91.5% for material, 95.8% for media, and 100% for linguistic aspects, indicating very high validity. Practicality tests yielded scores of 95% from educators and 90.2% from students, demonstrating very high practicality. These results indicate that the OIDDE-based e-module is highly valid and practical, making it a viable alternative teaching material for science learning. It is recommended that further development expand the module’s features and content scope to enhance its educational impact.